Revision of the Remaneicaris argentina-group (Copepoda, Harpacticoida, Parastenocarididae): supplementary description of species, and description of the first semi-terrestrial Remaneicaris from the tropical forest of Southeast Mexico - Corgosinho, Paulo Henrique C.; Mercado-Salas, Nancy F.; Arbizu, Pedro Martínez; Silva, Edinaldo Nelson Dos Santos; Kihara, Terue C. (Zootaxa, 2017)
Remaneicaris is a species-rich Neotropical monophyletic group, easily recognized by the synapomorphic position of the outer seta of the third exopodite of leg 4, localized at 2/3 of the outer margin. The genus, comprising 35 species in five monophyletic groups, plus R. ignotus and R. meyerabichi, retains an unusual set of plesiomorphic characters. Herein we supplement the descriptions of the species belonging to the Remaneicaris argentina-group, and describe a new species from the tropical forest of Southeast Mexico. The present study extends the geographic distribution of the genus, with the northernmost record until now being from El Salvador. The genus having hitherto been known from interstitial groundwater habitats, this is its first record in epigean semi-terrestrial habitats. Remaneicaris siankaan sp. nov. was found in phytotelmata (bromeliads), leaf litter, moist soil, permanent ponds (known locally as “aguadas”), and temporal and permanent wetlands (savannahs). The new species can be easily characterized by its finely pitted cuticle, the ε (epsilon)-shaped thumb of the male P3 and the bifid accessory spine with distal hyaline inner tip, which precedes the thumb. A new method for the 3D reconstruction of microcrustaceans is described.